Modeling a dependence system with specified conditions - Usenko, Valerii; Vorontsov, Oleg; Nikolaenko, Volodymyr; Usenko, Irina (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article describes the formation of a multidimensional geometric object that reflects a system of dependencies of many variables based on geometric modeling. It is noted that in the process of creating geometric objects, the tasks of fulfilling the specified conditions and the need to model dependencies between all or some parts of the variables of a given system arise. The article develops a technique for constructing multidimensional geometric objects formed by other manifolds of different sizes and weights. These types must satisfy the given conditions. The structure of a multidimensional figure is applicable for solving complex optimization problems with many criteria in computer-aided design environments.